Barley ABI5 (Abscisic Acid INSENSITIVE 5) Is Involved in Abscisic Acid-Dependent Drought Response - Collin, Anna; Daszkowska-Golec, Agata; Kurowska, Marzena; Szarejko, Iwona (Frontiers in Plant Science, 2020)
ABA INSENSITIVE 5 (ABI5) is a basic leucine zipper (bZIP) transcription factor which acts in the abscisic acid (ABA) network and is activated in response to abiotic stresses. However, the precise role of barley (Hordeum vulgare) ABI5 in ABA signaling and its function under stress remains elusive. Here, we show that HvABI5 is involved in ABA-dependent regulation of barley response to drought stress. We identified a barley TILLING mutant carrying a G1751A transition in the HvABI5 gene. The hvabi5.d mutant was insensitive to ABA during seed germination, yet it showed the ability to store more water than its parent cv. ‘Sebastian’ (WT) in response to drought stress. The drought-tolerant phenotype of hvabi5.d was associated with better membrane protection, higher flavonoid content and faster stomatal closure in the mutant under stress compared to the WT. The microarray transcriptome analysis revealed up-regulation of genes associated with cell protection mechanisms in the mutant. Furthermore, HvABI5 target genes: HVA1 and HVA22 showed their higher activity after drought, which may imply better adaptation of hvabi5.d to stress. On the other hand, chlorophyll content in hvabi5.d was lower than in WT, which was associated with decreased photosynthesis efficiency observed in the mutant after drought treatment. To verify that HvABI5 acts in the ABA-dependent manner we analyzed expression of selected genes related to ABA pathway in hvabi5.d and its WT parent after drought and ABA treatments. The expression of key genes involved in ABA metabolism and signaling differed in the mutant and the WT under stress. Drought-induced increase of expression of HvNCED1, HvBG8, HvSnRK2.1 and HvPP2C4 genes was 2 to 20 times higher in hvai5.d compared to ‘Sebastian’. We also observed a faster stomatal closure in hvabi5.d and much higher induction of HvNCED1 and HvSnRK2.1 genes after ABA treatment. Together, these findings demonstrate that HvABI5 plays a role in regulation of drought response in barley and suggest that HvABI5 might be engaged in the fine tuning of ABA signaling by a feedback regulation between biosynthetic and signaling events. In addition, they point to different mechanisms of HvABI5 action in regulating drought response and seed germination in barley.